Determination of CO₂ in packaged beer by a manual pressure/temperature (P/T) method – determination of the repeatability and reproducibility: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Castañé, F. X. (BrewingScience, 2005)
The determination of CO2 in packaged beer by a manual pressure/temperature (P/T) method was collaboratively tested by the Analysis Committee of the European Brewery Convention according to ISO Standard 5725 in order to determine its suitability for publication in Analytica-EBC. Repeatability (r95) and reproducibility (R95) values are presented.Repeatability (r95) was found to be independent on the mean value and was 0,12 g/l over the range 4,8 to 7,0 g/l. Reproducibility (R95) was found to be dependent on the mean and was 0,089m g/l over the range of CO2 tested.The method has acceptable repeatability and reproducibility and is recommended for inclusion in Analytica-EBC.At the same time an instrumental thermal conductivity method using the Micro Logger 3654 analyzer from Hach Ultra Analytics was also collaboratively tested in order to determine its repeatability (r95) and reproducibility (R95) values.Repeatability (r95) was found to be independent on the mean value and was 0,08 g/l over the range 4,7 to 6,9 g/l. Reproducibility (R95) was found to be dependent on the mean and was 0,054m g/l over the range of CO2 tested.The instrumental thermal conductivity using the Micro Logger 3654 analyzer from Hach Ultra Analytics is also recommended for inclusion in Analytica-EBC.